VOWEL PECULIARITIES ASSOCIATED WITH CULTUROHISTORICAL BOUNDARIES IN THE RUDZĀTI SUBDIALECT - Vilcāne, Ilona (Via Latgalica, 2016)
This article expands upon the findings of the paper presented at the 8th International Conference of Latgalistics. The study is based more generally upon the author’s study that forms the basis of the Master’s thesis “The culturohistorical circumstances of the development of the Rudzāti subdialect”.The Rudzāti subdialect is spoken in contemporary Līvāni municipality in the parish of Rudzāti, and also in section Z of Rožupe parish. The neighboring subdialect ZR is Atašiene, ZA – Stirniene, A – Preiļi, D – Vārkava, bet R – Līvāni.Since geographic, economic or political circumstances have differentiated groups of people (In Latvia, the largest factor is in the development of dialects has been the allocation of territory to different manor estates, Rudzīte 2005: 15), the aim of the research is to clarify which culturohistorical boundaries crossed the territory of the Rudzāti dialect until it became a single parish in 1925, which neighboring dialects influenced its development, and whether this is reflected in contemporary phonetic material, especially in the dialect’s vowel sounds.Interviews conducted for the 2010–2012 ESF project “Their nest, their land – Latvian rural population development strategy and cultural change” were used in the research (ESF 2010–2012). Three Rudzāti speakers from the ZA subdialect area were also interviewed (Speaker interviews, 2015).The most important factor in the analysis of the characteristics of the Rudzāti437 dialect was the gathering of the most accurate sociolinguistic information possible about the speakers. It was especially important to discern the places of birth and current residence of the speakers, in order to detect peculiarities in the “endpoints” of the Rudzāti437 dialect and isolate these. For this reason, it was also important to query the place of birth of speakers’ parents. Attention was also paid to each speaker’s religious confession and denomination. The Ošas river was used as a conditional boundary line during analysis of speaker material, because this was the boundary between the counties of Rēzekne and Daugavpils during the Russian Imperial period, and speakers of the dialect were grouped according to which side of the river their place of residence was located.In the study, correlations to the vowels and diphthongs of standard Latvian were analyzed in the Rudzāti dialect in addition to vowel deletions, reductions and insertions in the final syllables. Special attention was paid to instances in which vowel and diphthong shifts indicated the possibility of intersections with isoglosses. Such differences were found in shifts of the standard Latvian vowels e, ā, ē, ū and the diphthong ei.